SAT0198 Effect of Increased Sarilumab Dose on Efficacy and Safety Outcomes in Poorly Responding Rheumatoid Arthritis (RA) Patients: The Mobility Study. (9th June 2015) - Genovese, M.C.; Decktor, D.L.; Parrino, J.; Boddy, A.; Graham, N.
Abstract : Background: Sarilumab is a human monoclonal antibody directed against IL-6R and has been shown to be effective with subcutaneous (SC) dose regimens of 150 mg and 200 mg q2w in RA patients with active disease despite MTX. 1 These two sarilumab doses are being tested further in additional ongoing phase 3 studies. Objectives: To assess the impact on efficacy and safety in MOBILITY of increasing the sarilumab dose from 150 mg to 200 mg q2w in poor responders to the 150 mg dose (NCT01061736 ). Methods: In this post hoc analysis of MOBILITY, adults with moderate-to-severe active RA and inadequate response to MTX were randomized to Pbo + MTX, sarilumab 150 mg q2w + MTX and sarilumab 200 mg q2w + MTX. At Wk 16, patients who did not achieve ≥20% improvement in swollen joint count (SJC) and tender joint count (TJC) or who had a clear lack of efficacy in the opinion of the investigator were offered rescue therapy with open-label sarilumab 200 mg q2w in all 3 dose arms (Pbo, 150 mg q2w, 200 mg q2w). ACR20 and ACR50 responses and DAS28-CRP were evaluated at Wks 16, 24 and 52. Missing data was imputed as a non-response for ACR20 and ACR50. DAS28-CRP values were reported as observed. Results: 1197 patients were randomized to three treatment groups. A subset of each randomized group was rescued on or after Wk 16 (Table ). Patients in the rescued Pbo cohort (n=156) responded to the 200 mg sarilumab rescue dose with improved ACR20 and ACR50 responses and decreased DAS28 CRP mean values at Wks 24 and 52. The sarilumab 150 mg cohort rescued at Wk 16 (n=30) exhibited more pronounced responses at Wk 24 than the 200 mg cohort rescued at Wk 16 (n=28). The percentage of patients achieving LDAS (DAS28-CRP ≤3.2) at Wks 24 and 52 were similar for sarilumab 150 mg and 200 mg rescued cohorts. The 150 mg and 200 mg rescued cohorts demonstrated comparable improvement in both ACR and DAS28 measures of effect by Wk 52. Incidence of treatment emergent adverse events (TEAEs), serious adverse events, or adverse events leading to treatment discontinuation were similar in the open-label rescue and double-blind periods. Infections were the most frequently reported TEAEs in the open-label rescue period. Two patients died due to an AE with onset during the open-label rescue period. Conclusions: Rescue at Wk 16 with open-label sarilumab 200 mg q2w of RA patients who had a suboptimal response to sarilumab 150mg q2w appeared to have therapeutic value. The safety profile observed in the post-rescue period was generally consistent with that observed in the double-blind period. The open-label nature of rescue in this study may be a limitation; additional studies to confirm these findings and further delineate the possible benefits of sarilumab dose titration will be required. References: Genovese M et al. Abstr. No. EULAR14-SCIE-3001 presented at EULAR 2014, Paris, France. Acknowledgements: The study was sponsored by Sanofi and Regeneron Pharmaceuticals Inc. Editorial support was provided by Tara Miller of Envision Scientific Solutions and funded by Sanofi and Regeneron Pharmaceuticals Inc. Disclosure of Interest: M. C. Genovese Grant/research support from: Sanofi, Regeneron, Eli Lilly, Consultant for: Sanofi, Regeneron, Eli Lilly, D. L. Decktor Shareholder of: Johnson & Johnson, Employee of: Regeneron, J. Parrino Shareholder of: Merck, Regeneron, Employee of: Regeneron, A. Boddy Shareholder of: Sanofi, Employee of: Sanofi, N. Graham Shareholder of: Regeneron, Employee of: Regeneron